2021
DOI: 10.1108/ilt-07-2021-0284
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication efficiency of crankpin bearing using square-cylindrical textures of partial textures optimized by genetic algorithm

Abstract: Purpose This paper aims to propose an optimal design of the partial textures in the mixed lubrication regime of the crankpin bearing (CB) to maximize the CB's lubrication efficiency. Design/methodology/approach Based on a hybrid model between the slider-crank-mechanism dynamic and CB lubrication, the square-cylindrical textures (SCT) of partial textures designed on the CB’s mixed lubrication regime are researched. The effect of the density distributions of partial textures on CB’s lubrication efficiency is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The existing research indicated that the GA (genetic algorithm) has good and stable performance in multi-objective optimization. 1,14,2729 Thus, this research applies GA to search the optimum values of n = [ K r , l , C r , l , l x,y , K 1,2,3 , C 1,2,3 , K s , K n , C s ] T based on their boundary conditions to reach the minimum RMS azs . Based on the analyzed result of HPI, VPI, and NSI’s dynamic parameters, the boundary conditions of HPI, VPI, and NSI are defined via the ratios of α , α 1 , β , and λ as follows:…”
Section: Influence Of Dynamic Parametersmentioning
confidence: 99%
“…The existing research indicated that the GA (genetic algorithm) has good and stable performance in multi-objective optimization. 1,14,2729 Thus, this research applies GA to search the optimum values of n = [ K r , l , C r , l , l x,y , K 1,2,3 , C 1,2,3 , K s , K n , C s ] T based on their boundary conditions to reach the minimum RMS azs . Based on the analyzed result of HPI, VPI, and NSI’s dynamic parameters, the boundary conditions of HPI, VPI, and NSI are defined via the ratios of α , α 1 , β , and λ as follows:…”
Section: Influence Of Dynamic Parametersmentioning
confidence: 99%
“…Therefore, new isolation of the off-road vibratory roller cab combined by the pneumatic mounts and the HM (CPHM) was proposed. 13,17 The results showed that the vehicle's ride comfort was significantly improved in comparison with the cab's HM. However, both the vertical seat and the cab's pitching accelerations were still high.…”
Section: Introductionmentioning
confidence: 99%
“…12 To solve these issues, the different isolation mounts of the HM, pneumatic mounts, and combined pneumatic-hydraulic mounts were also proposed to improve the ride comfort of the off-road vibratory roller. 10,11,13,14 Based on the genetic algorithm (GA) and fuzzy-PID control, [15][16][17][18] the nonlinear damping force of the HM used on the off-road vibratory roller cab was then optimized and controlled. 19 The results showed that both the vertical driver's seat acceleration and the cab's pitching acceleration were significantly reduced by using the semi-active cab's HM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the textures of different shapes, they found that the flat texture showed the best loading capacity and the smallest friction coefficient. Xu et al (2021) studied the influence of local texture on the oil film pressure and friction coefficient of bearings and optimized the texture parameters through a genetic algorithm (GA). The results showed that, compared with a smooth surface, the optimized texture increased the oil film pressure by 8.2% and reduced the friction coefficient by 21.6%.…”
Section: Introductionmentioning
confidence: 99%